2005 IEEE International Symposium on Microwave, Antenna, Propagation and EMC Technologies for Wireless Communications
DOI: 10.1109/mape.2005.1617915
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time ISAR Image Synthesis of Ballistic Targets

Abstract: Digital image synthesis(DIS) is a specific we make several hypotheses: (1) the rocket has a counter-ISAR technique which employs a false target single-stage and the propellant is consumed during the synthesized to deceive the imaging radar. To make the burn time in a linear fashion;(2) all the forces act on one synthesized false missile images more actual, the point and the moment is not considered; (3) the distribution of the scattering centers for the according longitudinal axis of the missile is aligned wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Besides, US GBR-X has been used to detect ballistic target in favour of anti-missile system seeking and recognition. ISAR with high-resolution, all-day, all-weather and directly observational characteristics plays an important role in military field, which makes the active jamming to ISAR to be a new research area [3,4,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, US GBR-X has been used to detect ballistic target in favour of anti-missile system seeking and recognition. ISAR with high-resolution, all-day, all-weather and directly observational characteristics plays an important role in military field, which makes the active jamming to ISAR to be a new research area [3,4,6].…”
Section: Introductionmentioning
confidence: 99%
“…To ISAR deceptive interference, studied done in the technology of digital Anti-jamming of Inverse Synthetic Aperture Radar based on Slope-varying Linear Frequency Modulation Signal image synthesis (DIS) against chirp ISAR, concluded that the DIS combined with high-instantaneous-wideband digital RF memory (DRFM) can synthesise the jamming signal of false target [3]. Another sudy realised a deceptive jamming against ISAR in anti-missile system and studied the method by which the real-time echo signal of false ballistic targets is produced [4]. With the development of ISAR jamming technology, it is important to develop ISAR anti-jamming and strengthen the ISAR electromagnetic combating ability, but less research about ISAR antijamming is reported.…”
Section: Introductionmentioning
confidence: 99%